Corporate social responsibility practices and performance: the moderating effect of family control - Alzate Gómez, Juan Diego (2020)
Companies face pressures of legitimacy and social acceptance in the markets where they operate (Yang, Su, & Fam, 2012). These pressures are accentuated by new trends in sustainable development (Bonsón & Bednárová, 2015; Caravedo, 2011; Vives & Peinado- Vara, 2011). In this sense, corporate social responsibility (CSR) has become a valuable tool for companies in their search for legitimacy and recognition on the part of society. Understanding the relationship between CSR and economic performance enables companies to adopt practices based on complementarity between economic, social and environmental aspects that help improve their interests together with those of their stakeholders (Valenzuela, Jara-Bertin, & Villegas, 2015). In contexts characterized by a high degree of ownership concentration, such as the Colombian case, understanding this relationship can help family businesses increase their legitimacy and economic performance (Lindgreen, Swaen, & Johnston, 2009). The purpose of this descriptive-quantitative study was twofold. On the one hand, it seeks to determine the relationship between the implementation of CSR practices and economic performance. On the other, it seeks to identify the effect of family control on the CSR-Performance relationship. For this, we studied a sample of 55 companies listed on the stock exchange of Colombia during the period 2010-2017. The analysis was performed with multiple regression models estimated from the GMM method. Three findings are highlighted: (a) No evidence was found about a relationship between the family character and the adoption of CSR practices; (b) Evidence was found on a direct relationship between the adoption of CSR practices and economic performance; and (c) the family character does not influence the CSR-Performance relationship.